Prawne aspekty Funduszu Rozwoju Kultury Fizycznej = Legal aspects of Fund of Development of Physical Culture - Klimczyk, Agata (Journal of Education, Health and Sport, 2015)
Klimczyk Agata. Prawne aspekty Funduszu Rozwoju Kultury Fizycznej = Legal aspects of Fund of Development of Physical Culture. Journal of Education, Health and Sport. 2015;5(9):380-385. ISSN 2391-8306. DOI10.5281/zenodo.30951 http://dx.doi.org/10.5281/zenodo.30951 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A380-385 https://pbn.nauka.gov.pl/works/624466 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 25.08.2015. Revised 05.09.2015. Accepted: 12.09.2015. Prawne aspekty Funduszu Rozwoju Kultury Fizycznej Legal aspects of Fund of Development of Physical Culture Agata Klimczyk Nicolaus Copernicus University in Toruń Streszczenie Celem publikacji jest przedstawienie prawnych aspektów Funduszu Rozwoju Kultury Fizycznej. W pracy dokonano analizy aktów prawnych oraz posiłkowano się przeglądem specjalistycznej literatury. Wskazano że rozwój sportu w Rzeczypospolitej finansowany jest ze środków Funduszu Rozwoju Kultury Fizycznej oraz ze środków pieniężnych w ramach tego funduszu rozdzielanych pomiędzy potrzebami o charakterze regionalnym, a także ogólnopolskim. Stwierdzono, że w ramach funduszu finansowane są także ośrodki naukowo- dydaktyczne związane ze sportem przygotowujące młodych ludzi do rywalizacji sportowej. Słowa kluczowe: fundusz, kultura fizyczna, prawo. Abstract The main aim of this work is to show legal issues related to Fund of Development of Physical Culture. The author had analysed legal acts and reviewed specialist literature. It was presented that sport in Poland is funded by above- mentioned Fund. The author shows that financial support related to this Fund is earmarked for regional and nation wide issues. It was states that thanks to this support are financed sports scientific and sports schools in which young people are prepared to sports competition. Key words: fund, physical culture, law.